Government ideology and tuition fee policy: Evidence from the German states - Björn Kauder; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
In January 2005 the German Supreme Court permitted the state governments to chargetuition fees. By exploiting the natural experiment, we examine how government ideologyinfluenced the introduction of tuition fees. The results show that rightwing governmentswere active in introducing tuition fees. By contrast, leftwing governments strictlydenied tuition fees. This pattern shows clear political alternatives in education policyacross the German states: the political left classifies tuition fees as socially unjust; thepolitical right believes that tuition fees are incentive compatible. By the end of 2014,however, there will be no tuition fees anymore: the political left won four state electionsand abolished tuition fees. In Bavaria the rightwing government also decided to abolishtuition fees because it feared to become elected out of office by adhering to tuition fees.Electoral motives thus explain convergence in tuition fee policy.
Keywords: D72; I22; I28; H75; 330; Tuition fees; education policy; government ideology; partisan politics